2017
DOI: 10.1109/tcomm.2016.2647699
|View full text |Cite
|
Sign up to set email alerts
|

MISO Networks With Imperfect CSIT: A Topological Rate-Splitting Approach

Abstract: Recently, the Degrees-of-Freedom (DoF) region of multiple-input-single-output (MISO) networks with imperfect channel state information at the transmitter (CSIT) has attracted significant attentions.An achievable scheme is known as rate-splitting (RS) that integrates common-message-multicasting and private-message-unicasting. In this paper, focusing on the general K-cell MISO IC where the CSIT of each interference link has an arbitrary quality of imperfectness, we firstly identify the DoF region achieved by RS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…Finally, the performance benefits of the power-partitioning strategy relying on RS in the overloaded MISO BC with heterogeneous CSIT was confirmed using simulations at finite SNR in the presence of a diversity of channel strengths [35]. In particular, in contrast to the RS used in [13], [19], [30], [31], [34], [35], [39], [41], [42] that relies on a single common message, [40] (as well as [32]) showed the benefits in the finite SNR regime of a multi-layer (hierarchical) RS relying on multiple common messages decoded by various groups of users.…”
Section: B Rsma: Bridging the Extremesmentioning
confidence: 82%
See 2 more Smart Citations
“…Finally, the performance benefits of the power-partitioning strategy relying on RS in the overloaded MISO BC with heterogeneous CSIT was confirmed using simulations at finite SNR in the presence of a diversity of channel strengths [35]. In particular, in contrast to the RS used in [13], [19], [30], [31], [34], [35], [39], [41], [42] that relies on a single common message, [40] (as well as [32]) showed the benefits in the finite SNR regime of a multi-layer (hierarchical) RS relying on multiple common messages decoded by various groups of users.…”
Section: B Rsma: Bridging the Extremesmentioning
confidence: 82%
“…Second, we provide a general framework of multi-layer RS design that encompasses existing RS schemes as special cases. In particular, the single-layer RS of [19], [30], [31], [34], [35], [39], [41], [42] and the multi-layer (hierarchical and topological) RS of [32], [40] are special instances of the generalized RS strategy developed here. Moreover the use of RS was primarily motivated by multi-antenna deployments subject to multi-user interference due to imperfect CSIT in those works.…”
Section: B Rsma: Bridging the Extremesmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the achievable sum DoF of RS is 1+(K −1)δ, which is strictly larger than Kδ achieved with ZF. In subsequent works, RS has been shown to be a very promising strategy in a wide range of scenarios, namely future PHY layer strategy [14], massive MIMO [15], MIMO networks [16], [17], multi-group multicast [18] and under various performance metric, namely sum-rate maximization [19], max-min fairness [20]. However, the benefit of RS in the context of multiuser mmWave systems with hybrid precoding has never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…RS has also been considered for robust transmissions under bounded CSIT errors in [8]. Studies of massive MIMO and MISO networks using RS strategies have been reported in [9] and [10], respectively. RS has so far been studied and optimized using a linear precoding framework.…”
Section: Introductionmentioning
confidence: 99%